2018
DOI: 10.1111/socf.12437
|View full text |Cite
|
Sign up to set email alerts
|

Income Inequality, Globalization, and the Welfare State: Evidence from 23 Industrial Countries, 1990–2009

Abstract: The debate regarding the welfare state–weakening effect and the income inequality‐increasing effect of globalization remains a contentious issue among stratification scholars. For some, globalization increases income inequality, while for others, globalization has no, or a negligible, effect on income inequality. This study brings new evidence to bear on this debate by separately investigating effects of multiple indicators of globalization (international trade, foreign direct investment [FDI] and immigration)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 74 publications
(88 reference statements)
3
11
0
Order By: Relevance
“…For instance, the Gini coefficient is 24.86 in Sweden, 26.19 in Finland, 29.43 in France, 28.95 in Germany, and 37.96 in the United States. Consistent with previous research (Auguste 2018; Piketty 2014), the SWIID data show that the United States is among the leading advanced economies with economic inequality.…”
Section: Data Measurement and Methodssupporting
confidence: 88%
“…For instance, the Gini coefficient is 24.86 in Sweden, 26.19 in Finland, 29.43 in France, 28.95 in Germany, and 37.96 in the United States. Consistent with previous research (Auguste 2018; Piketty 2014), the SWIID data show that the United States is among the leading advanced economies with economic inequality.…”
Section: Data Measurement and Methodssupporting
confidence: 88%
“…Not surprisingly, welfare state retrenchment characterizes the recent experience of Western nations where inequality has been on the rise (Huber and Stephens, 2001; Korpi, 2003). Prior work on affluent nations shows that welfare generosity significantly reduces income inequality (Alderson and Nielsen, 2002; Mahutga et al, 2017), while a broader measure of government spending consistently shows negative effects, as well (Auguste, 2018; Brady and Leicht, 2008; Kollmeyer, 2015). By contrast, measures of government spending or tax revenue do not perform as well in studies featuring larger cross-national samples, displaying either no significant impact (Cole, 2015; Kerrissey, 2015; Wong, 2016) or a conditional effect (Lee, 2005a) on inequality.…”
Section: Theoretical Mechanismsmentioning
confidence: 99%
“…Moreover, to the extent that trade liberalization increases the demand for skilled (relative to unskilled) labor, this may elevate inequality levels, as well (Alderson and Nielsen, 2002; Rodrik, 1999). However, prior research lacks consensus, as studies find that international trade either increases (Auguste, 2018; Barro, 2008), reduces (Brady and Leicht, 2008; Wong, 2016), or does not significantly impact (Cole, 2015; Kollmeyer, 2015) income inequality. Research focused on affluent nations finds that ‘Southern imports’ (i.e., imports from less developed nations) are linked to growing inequality (Alderson and Nielsen, 2002; Kwon, 2014, 2016).…”
Section: Theoretical Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most influential accounts linking inequality and development is Kuznets’s (1955) hypothesis that income inequality increases as a country transitions to modernization, peaks at an intermediate level of development, and then decreases at advanced levels of development. However, while cross-sectional analyses have shown income inequality to be, on average, higher in less developed and developing countries than in advanced countries (Clark 2019; Nielsen 1994), recent income inequality upswings observed in many advanced economies have problematized the Kuznets proposition (Auguste 2018; Kwon and Salcido 2019; Piketty 2014). Still, research has found Kuznets’s core argument (that inequality is produced by social differentiations that are related to distinct stages of development) relevant for understanding recent trends in inequality (Clark 2019; Kwon 2016a; Milanovic 2016:50).…”
Section: The Theoretical Link Between Development and Inequalitymentioning
confidence: 99%